Group Investigation sebagai Proses Penanaman Sikap Toleransi Siswa Kelas IX dalam Pembelajaran IPS - Sri Wahyuni; Siti Maryam Yusuf (JIIPSI: Jurnal Ilmiah Ilmu Pengetahuan Sosial Indonesia, 2021)
Education in Indonesia is affected by global changes that demand to be more advanced. These socio-cultural changes and globalization have had negative and positive impacts, especially for the younger generation. Especially for moral degradation, educational institutions and all driving elements emphasize the importance of knowledge and the application of tolerance in everyday life in minimizing deviant behaviors that can be done by students. Therefore, it is necessary to have a learning strategy that can foster tolerance for students from an early age. This study aims to determine the application of group investigation in instilling tolerance for grade IX students in social studies learning at SMPN 1 Mlarak, with a qualitative research method design using documentation, observation, and interview methods. Based on the results of data analysis, it was found that (1) the application of the group investigation learning model included: selection of material topics, which were organized in the Chapter of Socio-Cultural Change and Globalization, cooperative planning, implementation, analysis and synthesis, collection of final results, evaluation. . (2) the inhibiting and driving factors come from innate attitudes, family, association, and society (3) The results of the cultivation of students' tolerant attitudes through the group investigation learning model are attitudes of religious tolerance, mutual help and cooperation incompleting assignments, an attitude of caring for others, and an attitude of tolerance without discriminating against other students in physical and academic terms.